Supporting a lifetime of fitness for the military veteran athlete: a narrative review - Tinney, Melissa J.; Nguyen, Chantal (Frontiers in Sports and Active Living, 2024)
The military veteran starts their career at peak physical fitness. Once injured or retired, physical activity for the veteran is integral to rehabilitation, recovery, and ongoing wellness. This may require adaptation for continued participation in physical activity. The military veteran, in the United States, has access to resources which can facilitate ongoing physical activity, engagement in competitive and recreational sports, no matter what age or ability. Reviewing the current literature will help understand the scope of programs available, their outcomes, and strategies employed to support a lifetime of fitness that may be applied to other populations and health care systems.